How does leadership style influence creative employee performance? - Yanto, Yanto; Arief, Mts; Setiadi, Nugroho J; Tjhin, Viany Utami (International Journal of Innovative Research and Scientific Studies, 2025)
The Indonesian dairy industry has minimal employee creativity. Many organizations do not pay attention to the fundamental capacity to encourage the creation of employee creative performance according to corporate strategy. The purpose of this study is to examine and analyze the influence of transformational leadership, creative self-efficacy, and organizational citizenship behavior on employee creative performance, with innovative work behavior and innovative climate as mediators in the dairy industry in Indonesia. This study involved 420 permanent employees in dairy industry companies. This study used primary data reinforced with confirmed secondary data. An interesting contribution of this study is the development of employee creative performance, proposing a model and conceptual framework for improving employee creative performance in the dairy industry. The results of the hypothesis test concluded that all relationships between variables were accepted, while the variables that were not accepted were: Transformational Leadership and organizational citizenship behavior, employee creative performance, and innovative climate, which did not moderate innovative work behavior to employees’ creative performance. The author offers a new model, the neo-configuration of an employee creative performance model. This model explains the role of innovative work behavior as a mediator of the factors that form employee creative performance and innovative climate as a moderator in dairy industry companies in Indonesia.